Cracking Assessment of Reinforced Concrete Slab Using Impact Hammer Test - Nor Hayati Abd Ghafar; Nuramieza Mohd Yazid (Journal of Structural Monitoring and Built Environment, 2024)
Impact hammer test is a vibration-based monitoring method used to detect cracking or damage in concrete structures by observing the vibration behavior such as the natural frequency, mode shapes and damping ratio. Damage or cracks in the structure can cause structure failure. The ability to quickly perform maintenance, if necessary, depends on the ability to identify damage or cracks. Concrete cracking has traditionally been detected via vibration analysis utilizing the impact hammer test. The main objectives of this research were to determine the natural frequency of the cracked and uncracked reinforced concrete slabs and to determine the depth of the crack using the impact hammer test. Two samples of reinforced concrete slabs were constructed in the laboratory. The reinforced concrete slabs were designed as Grade 25 concrete. After 28 days, the impact hammer test was conducted on the uncracked slabs. After that, the slabs were subjected to a four-point bending test with loads of 3 kN, 6 kN, 12 kN and 15 kN. For each load increase, the impact hammer test and the crack mapping were performed. The natural frequency of the cracked and uncracked slabs was compared after that. The natural frequency of both Slab 1 and Slab 2 decreased after the slab was cracked compared to before cracked. The width of the crack was also determined by analyzing the wave acceleration from the impact hammer test. The outcome demonstrated that the wave’s acceleration increased as it propagates through the crack region. The percentage difference in the waves’ acceleration was calculated. The result was also compared with crack depth measurement from PUNDIT. The result showed that the location of the maximum crack width and crack depth was the same. It also justified that when the percentage difference of the acceleration decreased, the crack width increased. However, in previous studies, these findings had not been discussed yet. Therefore, further research needs to be done to understand the propagation of the wave on the cracked slab to validate the findings.